2018
DOI: 10.3389/fimmu.2018.01693
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotype and Transcriptome Profile of Patients With Multiple Sclerosis Treated With Fingolimod: Setting Up a Model for Prediction of Response in a 2-Year Translational Study

Abstract: BackgroundFingolimod is a functional sphingosine-1-phosphate antagonist approved for the treatment of multiple sclerosis (MS). Fingolimod affects lymphocyte subpopulations and regulates gene expression in the lymphocyte transcriptome. Translational studies are necessary to identify cellular and molecular biomarkers that might be used to predict the clinical response to the drug. In MS patients, we aimed to clarify the differential effects of fingolimod on T, B, and natural killer (NK) cell subsets and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 69 publications
8
34
1
Order By: Relevance
“…Our study included higher numbers of Active patients (18 versus 8) selected using different criteria and also defined RTE differently. Moreno-Torres and colleagues 33 reported a higher pre-treatment CD56 bright NK cell frequency in patients who were subsequently stable versus active on FTY; a finding not replicated here. A cross-sectional study found higher CD56+ T-cell frequencies in FTY-treated versus untreated patients, and an even higher frequency of these cells during relapse in 4 patients 34 .…”
Section: Discussioncontrasting
confidence: 71%
“…Our study included higher numbers of Active patients (18 versus 8) selected using different criteria and also defined RTE differently. Moreno-Torres and colleagues 33 reported a higher pre-treatment CD56 bright NK cell frequency in patients who were subsequently stable versus active on FTY; a finding not replicated here. A cross-sectional study found higher CD56+ T-cell frequencies in FTY-treated versus untreated patients, and an even higher frequency of these cells during relapse in 4 patients 34 .…”
Section: Discussioncontrasting
confidence: 71%
“…As expected, genes related to the mechanism of action of an S1PR modulator, such as S1PR1 and CCR7, were downregulated, as reported with fingolimod (13,14). Furthermore, we found that siponimod exerted an antiinflammatory effect through the downregulation of AKT3, CD19, CD40, CD40L, IL23A, CXCR5, IL2RA, IL7R, IL23A, IL21R, IL11RA, IL6ST, CR2, and IRF4 genes, which is similar to what has been observed in RRMS patients treated with fingolimod (15). Consistent with the microarray analysis, significant reductions in the CD19 + B cell and CD4 + T cell populations were detected via immunophenotyping analysis.…”
Section: L I N I C a L M E D I C I N Esupporting
confidence: 89%
“…Interestingly, immunophenotyping analyses have shown that fingolimod and siponimod induce a reduction in circulating CD4+ T cells, CD8+ T cells (specifically a selective reduction of naïve and central memory T cells with a relative increase of peripheral effector memory T cells), as well as B cells, in patients with RRMS and SPMS, respectively [90][91][92]. Gene expression studies have also shown reductions in the expression of key inflammation-related genes with fingolimod in patients with RRMS [93] and with siponimod in patients with SPMS [91]. Additionally, siponimod was shown to shift the immune system toward an anti-inflammatory and suppressive homeostatic state through enrichment of regulatory T cells, transitional regulatory B cells and B1 subsets, possibly contributing to the clinical efficacy of siponimod in SPMS [91].…”
Section: S1pr Modulation and Effects On Lymphocytesmentioning
confidence: 99%